The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.21608/aja.2015.18444
|View full text |Cite
|
Sign up to set email alerts
|

New Applicable Approach to Examine The Leverage–Value Relationship

Abstract: Many literatures studied the relationship between the leverage and the value of firms. Some studies found no relationship and other studies show that the relationship is positive, however, another studies show that the relationship is negative. Therefore, the leverage-value relationship seems to be an unresolved puzzle in the capital structure empirical literature.Therefore, this study seeks to examine the leverage-value relationship to interpret the significant and the direction of this relationship by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…So negative relationship between the leverage factor and the average returns of 25 size-B/M portfolios is founded. This result on (lev) is similar to that shown by Mahran (2015) who found that in spite of the difference among firms in growth opportunities or in operating efficiency, the leverage (book or market) have a significant negative effect on both the firm value and the difference between firm value and the industry value in the Saudi stock market.…”
Section: G the Empirical Results Of Six-factor Modelsupporting
confidence: 86%
“…So negative relationship between the leverage factor and the average returns of 25 size-B/M portfolios is founded. This result on (lev) is similar to that shown by Mahran (2015) who found that in spite of the difference among firms in growth opportunities or in operating efficiency, the leverage (book or market) have a significant negative effect on both the firm value and the difference between firm value and the industry value in the Saudi stock market.…”
Section: G the Empirical Results Of Six-factor Modelsupporting
confidence: 86%